Design of an adaptive - passive dynamic vibration absorber composed of a string - mass system equipped with negative stiffness tension adjusting mechanism - Acar, Mustafa Ali. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2011., 2011)
In this study, a new adaptive-passive dynamic vibration absorber design is discussed. This proposed design is composed of a stiff string under tension with a central mass attachment as a dynamic vibration absorber (DVA), a negative stiffness mechanism as a string tension adjustment aid and a tuning controller to make it adaptive. Dynamic properties of adaptive-passive DVA systems are adjusted in real-time by generally varying their stiffness. The adaptive-passive DVA design subject to this thesis uses the string tension as a tuning parameter. The dependency of the natural frequencies of this system on the string tension is analyzed using finite element method and verified analytically. Additionally, a method for adjusting the string tension with almost zero effort is proposed. To achieve this goal, the design incorporated a negative stiffness element to create a quasi-zero stiffness and constant zero-force mechanism when combined with the string. Force-displacement analysis of a system composed of a pre-loaded spring and a rigid link is examined analytically. It was shown that the system can have constant negative stiffness behavior. A string tension adjustment algorithm is created which tunes the DVA system depending on the magnitude and frequency of the most dominant component of the vibration signal. Finally, a prototype of the complete design is built. A series of experimental procedures are conducted on the prototype with the intention of verifying the theoretical calculations. Results obtained from these experiments are also given in the thesis.
Keywords: Autonomous robots.; Intelligent agents (Computer software)